Case report: Abdominal mesothelioma in Atelerix albiventris - Troncoso, Ignacio; Brown, John; Isla, Carla; Lajara, Juan Manuel; Ebner, Max; Fehrmann-Cartes, Karen (Frontiers in Veterinary Science, 2024)
Hedgehogs, as exotic species, are more susceptible to various neoplastic conditions affecting diverse bodily systems, particularly the tegumentary, hemolymphatic, and digestive systems. Among these conditions, epithelial tumors are the most prevalent, followed by round cell tumors and mesenchymal tumors. A striking characteristic is the malignant nature of over 8% of these tumors, leading to a generally unfavorable prognosis. This study aims to present a unique case involving a 2.5 year-old male African pygmy hedgehog in Concepción, Biobío District, Chile, diagnosed with a mesenchymal neoplasia originating from mesothelial cells. The hedgehog presented to the veterinary clinic with acute abdominal pain, prompting ultrasound imaging, and comprehensive cytological, histopathological, and immunohistochemical analyses. During abdominal ultrasound, a mass was observed, and its cytological examination revealed the presence of malignant cells. The histopathological examination unveiled a diffuse mesothelial cell tissue interwoven with abundant fibrous tissue and small cysts containing serous fluid, all enveloped by flattened or cuboidal cells of mesothelial origin. Immunohistochemistry further confirmed the diagnosis, demonstrating positive immunostaining for calretinin and mesothelin markers, corroborating the diagnosis of fibrous malignant peritoneal mesothelioma. This case highlights the complexity of neoplastic conditions in hedgehogs and emphasizes the importance of multimodal diagnostic approaches for accurate identification and understanding of these rare diseases.